2008
DOI: 10.2151/jmsj.86.919
|View full text |Cite
|
Sign up to set email alerts
|

The Diurnal Cycle of Convection over the Northern South China Sea

Abstract: The diurnal cycle of convection over the northern South China Sea (SCS) during the onset of the summer monsoon is documented using data from the May−June 1998 South China Sea Monsoon Experiment (SCSMEX) and from ten years of observations from the Tropical Rainfall Measuring Mission (TRMM) precipitation radar.Results both during SCSMEX and from TRMM observations show a prominent signal of propagating convection over the northern SCS. In particular, convection is found to initiate just off the southern coast of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 37 publications
4
16
0
Order By: Relevance
“…Radar data from the R/V Ron Brown in the Bay of Bengal indicate that the convection associated with the diurnal signal has characteristics of squall lines with trailing stratiform precipitation. A southward propagation of convective systems over the South China Sea was also observed during the 1998 South China Sea Monsoon Experiment (SCSMEX), similar to that over the Bay of Bengal (Aves and Johnson 2008). The monsoon onset over the northern South China Sea (near 20°N) occurred around mid-May and is characterized by a regular signal of southward propagation of convection (low values of IR brightness temperature) at an approximate speed of 15 m s -1 (Fig.…”
Section: Diurnal Cycle In the Asian Monsoon Regionsupporting
confidence: 52%
See 3 more Smart Citations
“…Radar data from the R/V Ron Brown in the Bay of Bengal indicate that the convection associated with the diurnal signal has characteristics of squall lines with trailing stratiform precipitation. A southward propagation of convective systems over the South China Sea was also observed during the 1998 South China Sea Monsoon Experiment (SCSMEX), similar to that over the Bay of Bengal (Aves and Johnson 2008). The monsoon onset over the northern South China Sea (near 20°N) occurred around mid-May and is characterized by a regular signal of southward propagation of convection (low values of IR brightness temperature) at an approximate speed of 15 m s -1 (Fig.…”
Section: Diurnal Cycle In the Asian Monsoon Regionsupporting
confidence: 52%
“…Advective effects can be ruled out because these systems propagate approximately at right angles to the low-level southwesterly monsoon flow. Also, gravity current dynamics appear to be an unlikely explanation since the speeds of propagation (~15 m s -1 ) in both regions (Webster et al 2002;Aves and Johnson 2008) are too fast to be accounted for by the relatively weak cold pools observed in these regions. Gravity waves, however, may play some role.…”
Section: Diurnal Cycle In the Asian Monsoon Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies are usually confined to areas such as the South China Sea (Ohsawa et al 2001;Lu and Xu 2007;Aves and Johnson 2008;Li et al 2010) or to the several islands of China and Japan (Ramage 1952). Most of the studies reported a dominant early-morning diurnal peak in the oceanic areas and a propagating signal from the southern coastline of mainland China to the northern South China Sea southeastwardly.…”
Section: Introductionmentioning
confidence: 99%